Permanent catheter drainage system for palliation of diuretic‐resistant cardiac ascites. (9th December 2015) - Bevan, Jonathan; Penn, Lee‐Anne; Mitchell, Andrew R. J.
Abstract: We report the case of a 69‐year‐old man with dilated cardiomyopathy treated with a permanent catheter drainage system for diuretic resistant cardiac ascites. At 1 year follow‐up, the patient had no heart failure related hospitalisations, displayed improved quality of life measures and had incurred no complications related to the catheter. Permanent tunnelled catheters are widely used to treat malignant ascites but may also be considered for palliation of cardiac ascites.